Rancang Bangun Game Edukasi Pembelajaran Huruf Alfabet Pada Anak Usia Dini Menggunakan Metode Multimedia Development Life Cycle - Rosyida, Elviana; Listiyono, Hersatoto; Zuliarso, Eri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The rapid development of technology today affects children's education process, including the way material is delivered in teaching and learning activities. Early childhood, especially those aged 3-7 years, are more likely to be interested in creative learning methods. The learning-by-play approach makes the learning process fun for children, which significantly supports the mental development and potential of children. This research aims to develop an educational game for the introduction of alphabet letters as a learning media that can help increase children's interest and interest in learning increase children's enthusiasm for learning and familiarize them with the letters of the alphabet. The research method uses the Multimedia Development Life Cycle method, which is a method using the stages of concept, design, material collection, manufacture, testing, and distribution. The development of this educational game is designed with HTML5-based Construct2. The final result of this research is an educational game for introducing alphabet letters as a learning medium to make it easier for children to learn to recognize the letters of the alphabet because it not only presents entertainment but also acts as a learning medium.